ANALISIS RISIKO KESELAMATAN DAN KESEHATAN KERJA (K3) PADA PENGOPERASIAN MESIN PIERCING MILL DI PT RAINBOW TUBULARS MANUFACTURE - Astanto, Ardi; Zetli, Sri (Computer Science and Industrial Engineering, 2023)
The piercing mill machine is one of the machines used by the company PT Rainbow Tubulars Manufacturing in producing Oil country Tubular Goods (OCTG) seamless pipes. The work process in operating the piercing mill machine includes sprinkling salt and pushing the pipe directly exposed to high heat, noise, smoke and extreme dust. The company has established controls such as Personal Protective Equipment (PPE) and Occupational Safety and Health (OSH) training, but these control efforts have not been maximized, due to a lack of awareness and compliance in using Personal Protective Equipment (PPE). The purpose of this study is to identify the risks of operating a piercing mill machine using the Job Safety Analysis (JSA) method, calculate and analyze the value of the risk, and provide recommendations to the company. Research data was obtained by documentation, observation, interviews, and discussions with production supervisors and OSH experts. The results of this study obtained four job structures and 27 work stages and 31 sources of risk. There are three very high risks, including splashing of billet material with high temperatures, exposure to heat, dust and high noise. providing tools such as replacing tools that are no longer suitable for use.